Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Lanjut Usia (Lansia) Penderita Hipertensi di Puskesmas Kassi Kassi Kota Makassar - Indah Puspita Sari; Andi Asrina; Andi Nurlinda (Window of Public Health Journal, 2025)
Hypertension is one of the degenerative diseases that is widely experienced by the community and can even cause death. The older a person is, the greater the risk of experiencing hypertension. Many factors cause hypertension in the elderly, including psychological factors. Psychological factors that older adults with hypertension can cause are anxiety. So, the purpose of this study is the relationship between family support and anxiety levels in the elderly (elderly) with hypertension at the Kassi Kassi Health Center, Makassar City, in 2022. This type of research is observational analytic with a cross-sectional study design approach and a sampling technique. This study used the accidental sampling technique; the sample was 128 people. Data was taken using a univariate and bivariate analysis questionnaire with the chi-square test. The results of this study indicate a relationship between emotional support and anxiety levels in older adults with hypertension (p=0.000), there is no relationship between instrumental support and anxiety levels in older adults with hypertension (p=0.179), there is a relationship between information support and anxiety levels in older adults with hypertension (p=0.000), there is a relationship between appreciation support and anxiety levels in older adults with hypertension (p=0.000).